If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40a + 30b = 630 Solving 40a + 30b = 630 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-30b' to each side of the equation. 40a + 30b + -30b = 630 + -30b Combine like terms: 30b + -30b = 0 40a + 0 = 630 + -30b 40a = 630 + -30b Divide each side by '40'. a = 15.75 + -0.75b Simplifying a = 15.75 + -0.75b
| X^2+y^2-4x+6y+2k-1=0 | | G/12-13=14 | | 3+4x+20-30=90 | | X^2-3x-8=7x-29 | | x-2=x+12 | | 3.2-7y=16y-1.89 | | 3x+20x+60-x-3= | | 3x-20x+60-x+3= | | -18x+63= | | 2744)1/3 | | 3x+5(-4x+12)-(x-3)= | | 9x^2+12+4=6 | | 7(2x-1)+5y-6=3y-2(3y)+3 | | 2/3x9/8 | | (4x)m+(5x+1)+(5x+3)m=102 | | -3b-5b-2b=80 | | -12r+15r=21 | | 10z+2z-13z=45 | | 18a-14a=36 | | -3s+8s-10s=35 | | 6y-8y-y=27 | | 7t-4t=24 | | 6x+2-4x-8x=16x+12+3x | | x^2-6y+2x-3xy=0 | | -5r-2r-s=-16 | | Z^4-8z^2+16=0 | | ln(5-x)+ln(2-x)=ln(28-4x) | | 0=3x^2+6xy | | z^5-5z^3-36z=0 | | 6x*-4=-17x | | 6x*-4= | | 75x^2+30x+3= |